Pemanfaatan Teknologi Pendidikan: Peran Guru SD dalam Mengembangkan Pembelajaran Abad 21 berbasis Teknologi di SDN Jatimulyo 01 - Dwiyana, Vita; Yuliati, Yuliati; Musfardilah, Musfardilah; Priawasana, Endra (Lembaga Yasin AlSys, 2025)
This study is motivated by the limited research on the development of technology-based learning in rural elementary schools, despite the growing need for technological integration in 21st-century education. The aim of this research is to explore the role of teachers in developing technology-based learning at SDN Jatimulyo 01, Jenggawah District, Jember Regency. A descriptive qualitative method was employed, involving six teachers selected through purposive sampling. Data were collected through interviews, observations, and documentation, and analyzed thematically. The findings reveal that teachers have begun to utilize basic technologies such as projectors, educational videos, and limited digital platforms like WhatsApp and YouTube. The main challenges identified include inadequate infrastructure and a lack of professional development opportunities. These findings support digital constructivist theory, which positions teachers as facilitators in technology-enhanced learning processes. The study concludes that there is a pressing need to enhance teachers' capacity in ICT integration to support adaptive and relevant learning aligned with students' contemporary needs. The practical implications of this research include recommendations for the provision of adequate ICT infrastructure, continuous professional training, and the development of contextual learning models suited to rural elementary school environments.